Synergies of nutrient fractions for fertilization in agriculture - Adjei, Linda (SLU/Dept. of Biosystems and Technology (from 130101), 2022)
A few countries are controlling the worlds phosphate reserves and this raw material is depleting at a faster rate. Most of the mined phosphate rock comes from Morocco and the Russia area which has unstable security. Studies shows that about 40% of potash export and 28% of nitrogen and phosphorus (P) fertilizer products comes from the Russia area. The current conflict in this region has increased shortage of these fertilizers impacting prices to increase sharply. The need for the development of chemical fertilizer substitutes especially for P is crucial for importing countries, the world’s food security and the environment. For this reason, this study aimed to formulate a complete fertilizer product that included saturated Polonite which is a waste product of wastewater treatment with a proven record as a good substitute to chemical P fertilizer. Polonite (Po), soil (S), peat (Pe), poultry manure (Pm) and Biofer N15 (B15) were the materials used for the formulation of the fertilizer product. To select the best formulated product, an initial molybdenum blue spectrophotometric P and pH analysis was carried out on base substrates (S, S+Po, S+Po+Pe) and incubated substrates. Incubated substrates were divided into six groups that included both fertilized (base substrates with either Pm or B15) and unfertilized (Pe, S, S+Po, S+Po+Pe) substrates with varying Po content between 10% and 20%. They were kept in a dark chamber at 20oC for a 0 and 7 days’ period (week 0 to week 1). The final selected substrates were grouped into three according to their treatment namely; treatment O (S, S+Po, S+Po+Pe), treatment Pm (S+Pm, S+Po+Pm, S+Po+Pe+Pm) and treatment B15 (S+B15, S+Po+B15, S+Po+Pe+B15). The same method of P and pH analysis was conducted on the final selected substrates used for the pot experiment. For our study, calcium chloride extractable P (CaCl2P) and pHCaCl2 was measured whiles portions of the selected final substrates sent for lab analysis measured ammonium lactate extractable P (P-AL) and pHwater. The pot experiment was performed in a climate chamber in the Biotron at SLU to test the effect of the final selected substrates on the growth of Pacino cola sunflower variety. Results indicated that unfertilized substrates recorded low plant-available P as compared to fertilized substrates based on the results obtained from our study and lab analysis. Results from the lab analysis indicated that all substrate used for pot experiment obtained a pHwater of 5.8-6.7 suitable for sunflower growth. With the exception of Pe with low a pHCaCl2 of 2.73, all other substrates under initial, incubation experiment and final substrate analysis obtained a pHCaCl2 values within the range of 5.0-7.13. There were no significant changes in plant-available CaCl2P of incubated substrates from week 0 to week 1 but some changes in pHCaCl2 occurred in substrates S+Po and S+Po+Pe and S+Po+Pm. Results from the pot experiment found substrates fertilized with Pm and B15 had a significant impact on sunflower growth as compared to unfertilized substrates. However, the addition of Po had no significant effect on sunflower growth. Among the fertilized substrates, substrates fertilized with Pm performed better. Also, some deficiency symptoms on the plants were observed. It can be concluded that saturated Polonite together with poultry manure may increase plant available-phosphorus, pH and nutrient efficiency use by plant that can lead to increase in plant growth and yield. However, large portions may be needed to meet plant nutrient needs per hectare and it is suggested this formulated product should be used together with chemical fertilizers. Also, the effectiveness of Po as an alternative P fertilizer need to be verified from another experiment by using materials with less P content together with saturated Polonite.